Knowing illusion: bringing a Tibetan debate into contemporary discourse (Oxford University Press, 2021)
"The two volumes of this study examine fundamental issues in Buddhist thought and practice, particularly the implications of the two truths (relative and ultimate). If, as Buddhist sources claim, all perceptions are overlaid with error, is it possible to have confidence in our knowledge of the world? If buddhas only perceive reality as it is, does this entail that they are incapable of relating to ordinary beings, who view their environment through a lens of false imaginings? Taktsang Sherap Rinchen, a 15th century Sakya scholar, explored the philosophical and practical ramifications of Madhyamaka antifoundationalism and accused Tsongkhapa, one of Tibet's most influential thinkers, of a fundamental incoherence that stems from an attempt to bring together the Epistemology tradition-which posits reliable epistemic instruments-and Prāsaṅgika Madhyamaka-which rejects any attempt at foundationalism. Both Taktsang and Tsongkhapa claim to correctly interpret Nāgārjuna and Candrakīrti but draw vastly different conclusions from their respective readings. The controversy Taktsang sparked has its roots in Indian debates regarding the implications of the two truths. These were further developed in Tibet and engaged some of Tibet's best minds for centuries. Our study, the first book length discussion of this literature, situates it in philosophical perspective, drawing parallels with contemporary global philosophy, and it also draws out the implications of the debate for the entire Buddhist enterprise of making sense of the world and presenting a path capable of leading beings to buddhahood"--